2020
DOI: 10.3390/ma13061389
|View full text |Cite
|
Sign up to set email alerts
|

Harvesting Variable-Speed Wind Energy with a Dynamic Multi-Stable Configuration

Abstract: To harvest the energy of variable-speed wind, we proposed a dynamic multi-stable configuration composed of a piezoelectric beam and a rectangular plate. At low wind speeds, the system exhibits bi-stability, whereas, at high wind speeds, the system exhibits a dynamic tri-stability, which is beneficial for harvesting variable-speed wind energy. The theoretical analysis was carried out. For validation, the prototype was fabricated, and a piezoelectric material was bonded to the beam. The corresponding experiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Studies have shown that the energy harvester can generate sufficient power over a relatively large range of wind speeds. Wang et al 178 proposed a dynamic multi-stable structure consisting of a piezoelectric beam and a rectangular plate to achieve the harvesting of variable speed wind energy, as shown in Figure 18, which exhibits bistable features at low wind speeds and tri-stable characteristics at high wind speeds. Studies have shown that the system can maintain a large output in variable speed wind environments.…”
Section: Application Of Energy Harvesting Technologymentioning
confidence: 99%
“…Studies have shown that the energy harvester can generate sufficient power over a relatively large range of wind speeds. Wang et al 178 proposed a dynamic multi-stable structure consisting of a piezoelectric beam and a rectangular plate to achieve the harvesting of variable speed wind energy, as shown in Figure 18, which exhibits bistable features at low wind speeds and tri-stable characteristics at high wind speeds. Studies have shown that the system can maintain a large output in variable speed wind environments.…”
Section: Application Of Energy Harvesting Technologymentioning
confidence: 99%
“…Also, in an inverted flag configuration, a bluff body, e.g. a plate, a Y-shape or a cylinder can be attached to the free end of the beam to generate flow-driven fluctuating motions like flapping [10], snap-through [11] or galloping [12] for the purposes of wind energy harvesting based on piezoelectricity (if the cantilever is single-layered) [10,11] or triboelectricity (if the cantilever is multilayered) [10,12]. Adaptivity with respect to wind speed and direction can be added to inverted flag harvesters.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical studies are also useful to determine the best arrangement of the harvester composed of several basic piezo elements, exposed to a varying external force [ 5 ] or to model the effect of geometry parameters over the output power in order to get handy formulas [ 6 , 7 ]. Piezoelectrics can also be exploited to directly harvest the energy of variable-speed wind by means of a dynamic multi-stable flutter harvester [ 8 ]. Additionally, the search for new materials showing piezoelectricity is active.…”
mentioning
confidence: 99%